Experimental study on the thermal properties of lightweight aggregate concretes at different moisture contents and ambient temperatures. (1st October 2017) - Nguyen, L.H.; Beaucour, A.-L.; Ortola, S.; Noumowé, A.
Highlights: Twelve mixtures of LWAC made of LWA from three different natures were tested. Thermal properties of LWAC were measured at different temperatures and moisture content. The conductivity increases between 5 °C and 35 °C and then stabilizes between 35 °C and 50 °C. The thermal conductivity and specific heat of LWAC increase linearly with the moisture content. The increase of the moisture content results in a low variation (4%) of the thermal diffusivity. Abstract: This study reports the influence of moisture content and temperature on the thermal properties of lightweight aggregate concretes. Seven types of coarse and fine lightweight aggregates from three different natures were used. The thermal tests were performed on concrete samples at three different moisture conditions: dry state, partial saturation state and saturated state. At the dry state, measures have been taken at four different temperatures: 5 °C, 20 °C, 35 °C and 50 °C. The results show a great dependence of thermal conductivity and specific heat of lightweight aggregate concretes on the moisture content. However, concrete thermal diffusivity is not much influenced by the moisture state. These variations are discussed as a function of the type of lightweight aggregate and it volume fraction. The thermal conductivity increases with the temperature between 5 and 35 °C and then stabilizes between 35 and 50 °C.